2019
DOI: 10.1155/2019/4209475
|View full text |Cite
|
Sign up to set email alerts
|

GSK-3β at the Intersection of Neuronal Plasticity and Neurodegeneration

Abstract: In neurons, Glycogen Synthase Kinase-3β (GSK-3β) has been shown to regulate various critical processes underlying structural and functional synaptic plasticity. Mouse models with neuron-selective expression or deletion of GSK-3β present behavioral and cognitive abnormalities, positioning this protein kinase as a key signaling molecule in normal brain functioning. Furthermore, mouse models with defective GSK-3β activity display distinct structural and behavioral abnormalities, which model some aspects of differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
71
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(84 citation statements)
references
References 162 publications
(205 reference statements)
2
71
0
3
Order By: Relevance
“…Our findings showing GSK-3β-induced increases in theta and gamma spectral power are consistent with previous clinical reports examining oscillatory dysfunction in AD and schizophrenia, two disorders of cognitive dysfunction that also present with increased expression and activity of HIP and/or cortical GSK-3β [2][3][4]. For example, electroencephalogram (EEG) studies revealed that persons with AD or schizophrenia exhibit increased global theta power [47,48] and enhanced resting state and evoked gamma power has been reported for both disorders [49][50][51][52], with increased high gamma activity in schizophrenia inversely associated with cognitive performance both in patients and their first-degree relatives [51].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings showing GSK-3β-induced increases in theta and gamma spectral power are consistent with previous clinical reports examining oscillatory dysfunction in AD and schizophrenia, two disorders of cognitive dysfunction that also present with increased expression and activity of HIP and/or cortical GSK-3β [2][3][4]. For example, electroencephalogram (EEG) studies revealed that persons with AD or schizophrenia exhibit increased global theta power [47,48] and enhanced resting state and evoked gamma power has been reported for both disorders [49][50][51][52], with increased high gamma activity in schizophrenia inversely associated with cognitive performance both in patients and their first-degree relatives [51].…”
Section: Discussionsupporting
confidence: 92%
“…Glycogen synthase kinase-3β (GSK-3β) is a serine/threonine kinase with over 100 biological substrates [1] that has been repeatedly shown to play a critical role in the pathology of various neuropsychiatric and neurodegenerative diseases, and in particular those that present with cognitive dysfunction [2][3][4][5]. Whereas decreased GSK-3β activity has been implicated in autism [6][7][8], most often disorders of cognitive dysfunction are associated with increased activation of the kinase, the most widely studied being Alzheimer's disease (AD) [2,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…As discussed in previous reviews [19,51,76], GSK3β functions in the assembly and disassembly of synapses determining synaptic plasticity. Except for the wide-recognized role in the regulation of tau phosphorylation, GSK3β activity also participated in proper synaptic development [77,78] and neurotransmission [79,80].…”
Section: Discussionmentioning
confidence: 89%
“…Accumulating evidences argue that GSK-3, particularly β isomer, is implicated in cell loss through decreasing the threshold for the opening of the mitochondrial mega channel (Yang et al, 2017). At the same time, many studies demonstrated the involvement of GSK-3β in several NDD (Jaworski et al, 2019;Thomas et al, 2013;Matsunaga et al, 2019;Shahab et al, 2014;Sulaiman et al, 2019).…”
Section: Introductionmentioning
confidence: 95%